الوضع الإداري والأمني في لواء كركوك بعد ثورة 14 تموز 1958 - فليح، حسين علي; الجبوري، مريم محمود عيدان (الجامعة المستنصرية - كلية التربية الأساسية, 2018)
يعد لواء كركوك من الالوية العراقية المهمة اذ يحتل موقعا استراتيجيا مهما في شمال العراق جعله يكون حلقة وصل ما بين الشمال والجنوب، فضلا عن غناه بالموارد والثروات الطبيعية، والأهم من ذلك كله فهو يشكل عراقا مصغرا اذ يضم تركيبة اجتماعية ملونة متكونة من مختلف القوميات والاطياف من التركمان والعرب والأكراد، فضلا عن اختلاف الديانات والمذاهب ففيه المسلمون والمسيح واليهود سابقا لذلك كان من الطبيعي أن تحدث تغييرا ادارية وامنية في اللواء خلال العهد الجمهوري خلال المدة (1958-1968) ومن هنا تبرز اهمية البحث. قسم البحث على مبحثين رئيسيين، إذ جاء المبحث الأول بعنوان (كركوك في العهد الجمهوري الأول 1958-1963) الذي تناول اهم التغييرات الادارية والامنية التي طرأت على لواء كركوك خلال عهد عبد الكريم قاسم، اما المبحث الثاني فجاء بعنوان (أوضاع كركوك في العهد الجمهوري الثاني 1963-1968) الذي تناول التطورات الادارية والأمنية في كركوك خلال عهد عبد السلام عارف.
The Kirkuk Brigade is one of the important Iraqi brigades occupying an important strategic position in northern Iraq making it a link between the north and south As well as rich in resources and natural resources Most important of all it is a small Iraq with a colorful social structure composed of different nationalities and sects of Turkmen Arabs and Kurds As well as the difference of religions and doctrines in which Muslims Christ and Jews previously it was natural to make administrative and security changes in the General during the Republican era during the period (1958-1968) and here highlights the importance of research. Department of research on two main subjects The first topic was entitled (Kirkuk in the first republican era 1958-1963) which dealt with the most important administrative and security changes that occurred in the Kirkuk Brigade during the reign of Abdul Karim Qasim The second topic was entitled (The situation of Kirkuk in the second republican era 1963-1968) which dealt with the administrative and security developments in Kirkuk during the reign of Abdel Salam Aref.
Keywords: لواء كركوك -- العراق -- التطورات الإدارية -- الأمن القومي